Characteristics of pain in patients with pituitary adenomas: A cross‐sectional study. (16th January 2021) - Dallel, Sarah; Devoize, Laurent; Tauveron, Igor; Pereira, Bruno; Clavelou, Pierre; Maqdasy, Salwan; Moisset, Xavier; Dallel, Radhouane
Abstract: Background: This study determines the prevalence and particularities of headache and pain with neuropathic characteristics (NC) in a large French group of patients with pituitary adenoma (PA). Methods: Analysis of validated self‐administered questionnaires, radiological characteristics and treatment strategies of PA was performed. Results: Of the 221 sent questionnaires, 146 could be used for statistical analysis, 50% of which were completed by women. Among responders, 58.9% had pain: 30.1% migraine, 15.7% pain with NC and 13.1% other types of pain. Migraine was more common in patients with PA than in the general population (30.1% vs. 21.3%, p = .010) and attacks received appropriate treatment for less than 20% of these patients. Furthermore, the prevalence of chronic migraine was much higher than in the general population (6.8% vs. 2.2%, p = .003). Neuropathic pain was also more frequent in PA patients than in the general population (15.8% vs. 6.9%, p < .001). Neuropathic pain was most often located in the extremities and was frequently described as an 'electric shock', 'numbness', or 'pins‐and‐needles'. Multivariate analyses linked migraine to younger age, anxiety, pain with NC, and a visible tumour on MRI, regardless of its invasiveness or secretory nature. Conclusions: Migraine headaches and neuropathic pain are more frequent and disabling in PA patients than in the general population. Both types of pain are comorbid in PA patients and are poorly treated. Migraine is associated with the presence of a tumour. Thus, biological mechanisms of this relationship need to be characterized to design optimal treatments for these individuals. Significance: Migraine headaches and neuropathic pain are more common in PA patients than in the general population and are generally poorly treated. A systematic screening for migraine should be done by physicians in daily practice to provide adequate therapeutics.